Transcriptomic analysis of skin biopsies in Prurigo nodularis patients: with and without atopic dermatitis - Lee, So Yeon; Um, Ji Young; Kim, Han Bi; Yang, Hyun-Woo; Kwak, In Suk; Chung, Bo Young; Park, Chun Wook; Kim, Hye One (Frontiers in Immunology, 2025)
BackgroundNodular dermatitis (PN) is a severely itchy chronic skin disease with symmetrically distributed nodules, often linked to an atopic background in some patients. However, the pathogenesis of PN with atopic dermatitis remains unclear.ObjectiveThe objective of this study is to compare the transcriptomes from skin biopsies of prurigo patients with and without atopic dermatitis, aiming to identify unique gene expression patterns and gain insights into the molecular mechanisms underlying Atopic dermatitis Prurigo (ADP) and Non-Atopic dermatitis Prurigo (NADP).MethodWe conducted transcriptome analysis to compare gene expression between normal controls and atopic dermatitis patients, identifying DEGs and performing KEGG and GO analyses, along with correlations between disease severity and itch NRS.ResultsWe performed transcriptome profiling on 5 patients with ADP, 6 patients with NADP, and 6 healthy controls. Gene expression analysis revealed significant differences in inflammatory cytokines, suggesting that cytokine-mediated pathways play an important role in the pathogenesis of ADP. GO and KEGG analyses revealed cytokine-cytokine receptor interactions, with Th2 cytokines (SERPINB4, IL4R, IL24) upregulated in ADP and structural repair (BMP2) and metabolic genes (LEPR) elevated in NADP. Severity analysis showed positive correlations with SERPINB4, S100A8, IL24, and TGFB1, and negative correlations with BMP2, IL33, and LEPR. Keratinocyte hyperproliferation and inflammatory genes were commonly upregulated in both ADP and NADP.ConclusionThese results provide insight into the molecular mechanisms of PN, particularly in the context of atopic dermatitis, and highlight that immune dysregulation and impaired skin barrier function are key factors in pathogenesis.